2010
DOI: 10.1007/s00373-010-0898-9
|View full text |Cite
|
Sign up to set email alerts
|

The b-Chromatic Number of Cubic Graphs

Abstract: The b-chromatic number of a graph G is the largest integer k such that G admits a proper k-coloring in which every color class contains at least one vertex adjacent to some vertex in all the other color classes. It is proved that with four exceptions, the b-chromatic number of cubic graphs is 4. The exceptions are the Petersen graph, K 3,3 , the prism over K 3 , and one more sporadic example on 10 vertices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 13 publications
(2 reference statements)
1
15
0
Order By: Relevance
“…The following theorem is proven by Jakovac and Klavzar in [15]. They showed that, except for four simple graphs, the b-chromatic number of connected cubic graph is 4.…”
Section: Some Known Resultsmentioning
confidence: 95%
“…The following theorem is proven by Jakovac and Klavzar in [15]. They showed that, except for four simple graphs, the b-chromatic number of connected cubic graph is 4.…”
Section: Some Known Resultsmentioning
confidence: 95%
“…[8,19]). The b-chromatic number of regular graphs has been investigated in a series of papers [6,17,20,22]. Determining the b-chromatic number of a tight graph is NP-hard even for a connected bipartite graph [18] and a tight chordal graph [12].…”
Section: Tablementioning
confidence: 99%
“…This bound was later improved to 2d 3 in [5]. In particular, it was shown in [18] that there are only four exceptions among cubic graphs with ϕ(G) < 4, one of them being the Petersen graph.…”
Section: Introductionmentioning
confidence: 99%